Pengembangan Buku Teks Berbasis Budaya Lokal (Lego-Lego) Sebagai Sumber Belajar IPS Untuk Pengutan Pendidikan Karakter Siswa di Sekolah Dasar - Jon Abraham Lalang Yame; Waspodo Tjipto Subroto; Agus Suprijono (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Indonesia is experiencing a crisis of love for the nation influenced by the lifestyle and culture of western nations who enter Indonesia. The key to this crisis lies in human resources. For this reason, it is necessary to improve the quality of human resources through the formation of national character. The occurrence of conflicts in Alor Regency is mostly caused by minor problems, which is due to the unfavorable character of the community. Efforts to prevent all forms of horizontal conflict that occur in society through local cultural values as a strengthening of character education in the life of the Alor community. One is the Lego-Lego culture. Lego is a social capital that has been inherited by the ancestors of the Alor community. The lego-lego dance contains a very deep meaning through the values implied in poetry or rhymes which are not only useful for fellow people in an effort to strengthen relationships between individuals, build unifying values, form community character, and the government. In relation to the need for teaching materials in the form of text books based on culture and local wisdom in Alor, it is necessary to study the development of local culture and wisdom, namely Lego-lego as social studies learning resources to improve student character education. This study uses a development method with a Four-D model consisting Define, Design, Develop and Disseminate with data collection techniques using observation, questionnaires and interviews. Data analysis was carried out descriptively qualitatively and quantitatively. The results of the study indicate that textbook teaching materials are very significant in improving students' abilities and forming student character through social studies learning in elementary schools related to local culture of Lego-lego.